Artist's Painting Techniques - Edited by Bridle, Bob (London Dorling Kindersley, 2016)
Whether you are trying your hand at painting for the first time or honing your artistic ability, this is the handiest guide to teach you how to paint. Starting with the basics such as observational skills and learning how to draw, this book will guide you into working with watercolours, acrylics, and oil paints. Learn everything you need to know about tone, colour, pattern, brushwork, and composition to create your own masterpieces with confidence. Embark on exciting artistic exercises and projects to discover your style and grow as an artist.
Include Color Illustrations, Glossary and Index
Keywords: Drawing -- Technique -- Painting -- Technique